Synergistic Transformational Leadership and Academic Culture on The Organizational Performance of Islamic Higher Education in LLDIKTI Region IV West Java - Ika Kartika; Saep Saepudin; Yanti Hasbian Setiawati (Jurnal Dirosah Islamiyah, 2022)
This study focuses on increasing the effect of synergistic transformational leadership and academic culture on organizational performance. This study aims to determine and analyze the positive effect of synergistic transformational leadership and academic culture on organizational performance. This research uses quantitative research method. The sample was determined randomly amounting to 145 people. Data collection tools use instruments that are distributed to research respondents. The data were analyzed using the Path Analysis model, which is to analyze the positive effects of synergistic transformational leadership and academic culture on organizational performance. The results of this study indicate that there is a positive influence of academic culture and synergistic transformational leadership on organizational performance and there is a positive influence of Synergistic Transformational Leadership on academic culture. To improve the organizational performance, it is necessary to increase synergistic transformational leadership and academic culture. Keywords: Synergistic Transformational Leadership, Academic Culture, Organizational Performance.